2021
DOI: 10.1016/j.celrep.2020.108583
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Regulation of Host Energy and Oogenesis by Microbiome-Derived Mitochondrial Coenzymes

Abstract: Gut microbiota have been shown to promote oogenesis and fecundity, but the mechanistic basis of remote influence on oogenesis remained unknown. Here, we report a systemic mechanism of influence mediated by bacterial-derived supply of mitochondrial coenzymes. Removal of microbiota decreased mitochondrial activity and ATP levels in the whole-body and ovary, resulting in repressed oogenesis. Similar repression was caused by RNA-based knockdown of mitochondrial function in ovarian follicle cells. Reduced mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 78 publications
1
34
0
Order By: Relevance
“…FAD participates in the execution of many functions. 15 FAD is the strongest free radical scavenger, and glutathione (GSH) constitutes the most important antioxidant barrier for cells. FAD can also convert homocysteine into S- adenosyl methionine (SAM), thereby avoiding the accumulation of homocysteine.…”
Section: Resultsmentioning
confidence: 99%
“…FAD participates in the execution of many functions. 15 FAD is the strongest free radical scavenger, and glutathione (GSH) constitutes the most important antioxidant barrier for cells. FAD can also convert homocysteine into S- adenosyl methionine (SAM), thereby avoiding the accumulation of homocysteine.…”
Section: Resultsmentioning
confidence: 99%
“…Beta oxidation is prone to congestion because of competition between longer and shorter acyl-CoA molecules for the same dehydrogenase enzymes, also leading to moderate accumulation of acylcarnitines. Such congestion can result from increased supply of long-chain fatty acids to mitochondria, insufficient capacity of the TCA cycle, or deficiency of oxidized forms of the key electron carriers FAD and NAD + (van Eunen, et al 2016; Gnainsky, et al 2021). The latter may in turn result from a backlog of the reduced forms FADH 2 and NADH at the electron transport chain or from general deficiency of those cofactors.…”
Section: Discussionmentioning
confidence: 99%
“…Aldh expression and the normal oogenesis phenotype could be restored by re-introduction of a specific Acetobacter gut bacterium to the flies. Gnainsky et al (2021) suggested that specific gut bacteria provision an essential B vitamin (riboflavin) and mitochondrial co-enzymes to the host to support oogenesis. While further research is needed to elucidate the involvement of these molecular pathways in microbiome-dependent egg production in D. suzukii , our study is the first to discover that the microbiome-dependent effects on egg production could have an effect on the foraging behavior of the host insects.…”
Section: Discussionmentioning
confidence: 99%